Análise da demanda e modelos de preços hedônicos no mercado imobiliário da cidade de Fortaleza - Souza Filho, Edmar Honorato de (2004)
The present work consists of the study of the economical determinants that contribute to the formation of the prices of the real estate market of the city of Fortaleza (Ceará), in the optics of the economical agents of demand, based in the hedonic or implicit prices theory. The model considered for the work investigates implicit prices in the curve of utility of an agent of demand segmented in two groups: direct consumer of the good house and the investor in properties, that it incorporates economical-financial additionally that measure the degree of risk and return in the formation of the hedonic prices. The study esteem the hedonic prices through a regression segmented by type of property of the prices observed against the several attributes distributed in the vectors of physical, location, economical and financial characteristics. The sample selected for estimate of the model is formed by the real estate transactions of occured launchings in the city (period from 1995 to 2003), as well as urban lands (period from 1995 to 1998), totalize the sum of 4.467 real estate occurrences, being 876 residential apartments, 1969 flats, 539 lands and 1622 commercial rooms. The work still investigates the main characteristics of the real estate market, it esteem the function of real estate demand for the city of Fortaleza, supplying diagnosis of the habitation dynamics of that metropolis and identifies the behavior of real estate risk of the quarters of the city of Fortaleza.